Understanding Nonsuicidal Self-Injury: Origins, Assessment, and Treatment. 2009
DOI: 10.1037/11875-005
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal models of nonsuicidal self-injury.

Abstract: Once considered a behavior restricted to individuals with developmental disabilities or with borderline personality disorder (BPD), nonsuicidal selfinjury (NSSI) is a remarkably common phenomenon exhibited by youth and adults with a range of diagnostic profiles. Recent estimates suggest that NSSI occuts at significant rates among preadolescents (7%; Hilt, Nock, Lloyd-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
58
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 85 publications
12
58
0
Order By: Relevance
“…Despite these limitations, the current research provides a direct test of several key tenets of extant interpersonal models of NSSI (Nock, 2008;Prinstein et al, 2009;Yates, 2004). Consistent with these models, results suggest that individuals who engage in NSSI are less likely to perceive their interactions with peers as supportive and to seek support to cope with distress on a daily basis-differences that are accounted for by greater social anxiety and tendency to rely on intrapersonal (vs. interpersonal) coping strategies during times of distress.…”
Section: Discussionsupporting
confidence: 50%
See 4 more Smart Citations
“…Despite these limitations, the current research provides a direct test of several key tenets of extant interpersonal models of NSSI (Nock, 2008;Prinstein et al, 2009;Yates, 2004). Consistent with these models, results suggest that individuals who engage in NSSI are less likely to perceive their interactions with peers as supportive and to seek support to cope with distress on a daily basis-differences that are accounted for by greater social anxiety and tendency to rely on intrapersonal (vs. interpersonal) coping strategies during times of distress.…”
Section: Discussionsupporting
confidence: 50%
“…Moreover, although interpersonal functions of NSSI were endorsed less frequently than intrapersonal functions of this behavior, both interpersonally oriented emotions (e.g., feeling rejected by and angry toward others) and intrapersonally oriented emotions (e.g., anger toward self, selfhatred) increased the odds of acting on NSSI thoughts . Similarly, although Snir and colleagues (2015) found that adults with borderline and avoidant (Nock, 2008;Prinstein et al, 2009;Yates, 2004). Examining day-to-day patterns of interpersonal experiences may help clarify whether the interpersonal problems relevant to NSSI are related to the quantity or quality of interpersonal behaviors.…”
mentioning
confidence: 99%
See 3 more Smart Citations